Development of fried chicken skin as a snack - Ganesan, Manirethnam; Getty, Kelly J.K. (My University, 2018)
Through Strength, Weakness, Opportunity and Threat (SWOT) analysis on Nasi Kandars (restaurants) in Southeast Asian countries, it was found that fried chicken skins may have potential as a new food product. The objective was to develop a method to produce a fried chicken skin snack and to determine differences between chicken skin from thighs and breasts. Chicken skin was removed from breast portions (BP) of three birds and thigh portions (TP) from eight thighs. Skins then were frozen for approximately 3 h at -18°C and then excess fat was removed. Skins were cut into 2 × 2” pieces and weight and thickness of the skin was measured in three places with a digital caliper. Next, skins were blanched at 100°C for 20 s, and placed in tap water (14°C) for 2 min. Black pepper and salt were applied after cooling. Parchment paper was placed below and on top of skin, set on a baking sheet with another sheet positioned on top to reduce skin curling and baked at 121 °C for 10 min. After each processing step, skins were measured for thickness, weight, and dimensions. Skins were frozen at -18°C for 3 h and fried at approximately 192°C for 3 min using peanut and vegetable oil. Color measurements, texture analysis, water activity, nutrition analysis, and a consumer preference test was conducted to determine differences between TP and BP skins. For all measurements at least 2 samples per bird or per thigh were evaluated. Initial skin thickness for TP and BP were 2.91±0.9 and 1.89±0.5 mm, whereas average weight losses (initial weight to fried weight) were 79.2% and 72.1%. TP and BP skin shrank to approximately 42% and 35% after frying. Skin from BP had a more uniform shape and size compared to TP skin. Water activity for BP and TP were 0.425 and 0.543. Color measurements were similar for BP and TP and nutritional analysis showed TP to have 3% higher fat than BP. Texture analysis observed that TP was crispier than BP and consumers (n=8) preferred TP over BP. A method for processing TP and BP skin was developed that produced a crispy, fried chicken skin with TP being preferred over BP.
Keywords: Spring 2018